2017
DOI: 10.1186/s12912-017-0226-2
|View full text |Cite
|
Sign up to set email alerts
|

The challenges and opportunities of translating best practice immunisation strategies among low performing general practices to reduce equity gaps in childhood immunisation coverage in New Zealand

Abstract: BackgroundImmunisation coverage rates vary considerably at the local level across New Zealand and challenges remain with effectively translating best available research evidence into public health practice. This study aimed to translate best practices from high performing general practices into strategies to improve childhood immunisation coverage among low performing practices.MethodsAn intervention study was undertaken of general practices with low immunisation coverage rates and a high percentage of the enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Individuals who decide not to vaccinate or were still undecided are often influenced by their perception of low likelihood of disease [ 14 , 37 ], because they do not usually get vaccinated [ 19 , 37 ], or because they do not consider it a priority [ 43 ]. Interviews with Māori women and Māori health providers about maternal vaccinations found the health providers often noting women not prioritising vaccinations [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who decide not to vaccinate or were still undecided are often influenced by their perception of low likelihood of disease [ 14 , 37 ], because they do not usually get vaccinated [ 19 , 37 ], or because they do not consider it a priority [ 43 ]. Interviews with Māori women and Māori health providers about maternal vaccinations found the health providers often noting women not prioritising vaccinations [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that there is crossover from findings from studies from over a decade ago [ 36 , 37 ] indicate that further strategies are required for effective change to improve maternal vaccination rates, particularly for Māori or Pacific women who have inequitable maternal vaccination coverage. Recommendations to improve vaccination coverage have ranged from additional funded visits to GPs and nurses to discuss immunisations [ 17 ], training of health care professionals [ 50 ], funded availability through pharmacies [ 51 ], administration in the antenatal visit setting, constant vaccine reminders throughout pregnancy [ 18 , 43 ], large public health campaigns, and removal of barriers to access [ 42 ]. Ultimately, a multi-pronged method to enhance vaccination uptake is needed, with improving knowledge of vaccination in pregnancy underpinning the approach.…”
Section: Discussionmentioning
confidence: 99%
“…This survey concluded that health care professionals needed to be aware of differing health beliefs amongst ethnic groups to enable them to tailor their consultations to address cultural-specific vaccine concerns (Greenfield et al, 2015). Tailoring consultations to a specific ethnic group to increase immunisation uptake was found to be effective in an intervention study in New Zealand (Turner et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A universal set of messages will not by itself improve adult immunization rates and recent studies highlight the critical need for various tools and strategies commensurate with the characteristics of the populations [19]. Incorporating a framework that considers these determinants in vaccine policy design and implementation will foster immunization equity among the most at-risk populations against seasonal influenza and other respiratory vaccine-preventable diseases [20].…”
Section: Social Determinants and Immunizationmentioning
confidence: 99%